The intracranial branch; A rare anatomical variation of the recurrent laryngeal nerve; Case report. (January 2021) - Moradi, Arash; Hajian, Abbas
Highlights: Intracranial branch of the RLN is a very rare variation with 0.2% prevalence rate. We reported this rare RLN variation in the right side and unilaterally. The RLN injury during thyroid surgery is common and surgeon needs to know now the anatomical variation well. Abstract: Introduction: The recurrent laryngeal nerve (RLN) originates from the Vagus nerve intrathoracically. It passes through the tracheoesophageal groove (TEG) in the neck and different variations in this section were observed. The RLN is at highest risk for injury during the thyroid surgery. Therefore, it is important to know variations to decrease the injury effectively. Presentation of case: A 50 years-old woman with no thyroid related complaints except for enlargement of the thyroid gland in recent 12-months that annoyed her during neck movement and for aesthetic features. Medical, surgical, drugs, irradiation history, laboratory data, and physical examination was unremarkable except for multi-lobulated enlarged thyroid gland. The CT scanning study revealed intrathoracic extension of the gland. Patient underwent total thyroidectomy with suspicious diagnosis of multinodular goiter which was confirmed later by pathologic study. Intraoperative exploration of the right RLN discovered an intracranial branch originating from the recurrent laryngeal trunk just beneath the inferior thyroid artery (ITA) at the level of the nerve intersection. The branch then passed laterally about 1 cm and penetrated in ipsilateral carotid sheath. Discussion: The RLN has different anatomical variations in either the right or the left side of the neck. However extra-laryngeal nerve branching is the most common variation but other seldom variations including the non-RLN, and intracranial branch should be mentioned by surgeon intraoperatively. Conclusion: To decrease iatrogenic injuries to RLN and its associated nerve branches knowledge of the nerve anatomy is mandatory for surgeon to prevent morbid side effects.